TRANSFORMASI DIGITAL UANG DAN EFEKTIVITAS TRANSMISI KEBIJAKAN MONETER DALAM SISTEM PERBANKAN HYBRID: TINJAUAN SISTEMATIS LITERATUR - Ahmad Rizani; Tehedi (CV. Adiba Aisha Amira, 2026)
The digital transformation of money has shifted the paradigm of global monetary architecture from a system based on conventional bank intermediation towards a hybrid financial ecosystem that integrates Central Bank Digital Currency (CBDC), real-time digital payments, and non-bank fintech platforms. This structural shift challenges the effectiveness of traditional monetary policy transmission mechanisms, which have long relied on interest rate, credit, and exchange rate channels via commercial banks. This article aims to critically examine the impact of the digital transformation of money on the effectiveness of monetary policy transmission within the context of a hybrid banking system through a systematic literature review. The research findings identify two main conclusions: (1) the digitalisation of money accelerates the speed of policy interest rate pass-through through increased digital competition, price transparency, and payment channel efficiency, whilst simultaneously introducing risks of liquidity volatility and commercial banking disintermediation that may weaken transmission stability; (2) the effectiveness of transmission within hybrid systems is highly heterogeneous across jurisdictions, depending on the maturity of digital infrastructure, the design of the CBDC architecture, levels of financial literacy, and the regulatory framework coordinating monetary authorities with technology regulators. Thus, there is no universal model for optimising monetary transmission in the digital age; each country requires a contextual approach that balances innovation with prudence, efficiency with inclusion, and policy precision with systemic stability. Recommended policy implications include designing CBDCs with tiered remuneration features, expanding access to emergency liquidity facilities for systemic non-bank institutions, strengthening inter-authority coordination, and significant investment in cyber resilience and digital financial literacy. This research contributes to the literature on digital monetary economics by providing the first comprehensive synthesis integrating perspectives on CBDCs, digital payment systems, and hybrid banking dynamics within a coherent analytical framework.